The right place at the right time: chaperoning core histone variants. (12th October 2015) - Mattiroli, Francesca; D'Arcy, Sheena; Luger, Karolin
Abstract: Histone proteins dynamically regulate chromatin structure and epigenetic signaling to maintain cell homeostasis. These processes require controlled spatial and temporal deposition and eviction of histones by their dedicated chaperones. With the evolution of histone variants, a network of functionally specific histone chaperones has emerged. Molecular details of the determinants of chaperone specificity for different histone variants are only slowly being resolved. A complete understanding of these processes is essential to shed light on the genuine biological roles of histone variants, their chaperones, and their impact on chromatin dynamics. Abstract : This review assesses the determinants of the specificity in histone variant‐histone chaperone interactions at the molecular and atomic level, and discusses biological roles of histone variants and chaperones.